Tin(IV)Porphyrin-Based Porous Coordination Polymers as Efficient Visible Light Photocatalyst for Wastewater Remediation - Nirmal Kumar Shee; Hee-Joon Kim (Nanomaterials)
Two porphyrin-based polymeric frameworks, SnP-BTC and SnP-BTB, as visible light photocatalysts for wastewater remediation were prepared by the solvothermal reaction of trans-dihydroxo-[5,15,10,20-tetrakis(phenyl)porphyrinato]tin(IV) (SnP) with 1,3,5-benzenetricarboxylic acid (H3BTC) and 1,3,5-tris(4-carboxyphenyl)benzene (H3BTB), respectively. The strong bond between the carboxylic acid group of H3BTC and H3BTB with the axial hydroxyl moiety of SnP leads to the formation of highly stable polymeric architectures. Incorporating the carboxylic acid group onto the surface of SnP changes the conformational frameworks as well as produces rigid structural transformation that includes permanent porosity, good thermodynamic stability, interesting morphology, and excellent photocatalytic degradation activity against AM dye and TC antibiotic under visible light irradiation. The photocatalytic degradation activities of AM dye were found to be 95% by SnP-BTB and 87% by SnP-BTC within 80 min. Within 60 min of visible light exposure, the photocatalytic degradation activities of TC antibiotic were found to be 70% by SnP-BTB and 60% by SnP-BTC. The enhanced catalytic photodegradation performances of SnP-BTB and SnP-BTC were attributed to the synergistic effect between SnP and carboxylic acid groups. The carboxylic acid connectors strongly resist the separation of SnP from the surface of SnP-BTB and SnP-BTC during the photodegradation experiments. Therefore, the high degradation rate and low catalyst loading make SnP-BTB or SnP-BTC more efficient than other reported catalysts. Thus, the present investigations on the porphyrin-based photocatalysts hold great promise in tackling the treatment of dyeing wastewater.